The relationship between spiritual consciousness and pain - Heng, Aik Teng; Leong, May Ho (INTI International University, 2020)
According the book Yellow Emperor's Internal Classic (Huang Di Nei Jing) of Traditional Chinese Medicine record that sensation is related to spiritual consciousness. Pain is also a kind of sensation, which can be transferred or alleviated by regulating mental consciousness, thus providing clinical guidance for the treatment of painful diseases. Various research data are cited to support this point. According to the discussion, if more people around the patient participate in calming the patient, it may have a better effect.